Sistem Pendukung Keputusan Pemeliharaan Stasiun Pengamatan Cuaca Di BMKG STAKLIM I Palembang - Hakim, Muhammad Abdul Azizul; ., Yulistia (MDP Student Conference, 2024)
The maintenance of weather observation equipment at the Class I Climatology Station in South Sumatra is not yet optimal, marked by delays in identifying weather data anomalies, an unsystematic decision-making process, and inefficient notification of problematic data. This study aims to develop a decision support system (DSS) with the Fuzzy AHP method to improve efficiency, objectivity, and decision-making speed. The DSS developed using the Fuzzy AHP method is able to overcome the existing problems. The system is able to display data in real-time, perform automatic evaluation, and use the Fuzzy AHP method to provide more accurate assessments. Overall, the system developed has successfully met the research objectives.